Multidisciplinary team meetings and their impact on work-flow in Radiology and Pathology Departments - KANE, BRIDGET THERESA; LUZ, SATURNINO; O'BRIAIN, DONAL SEAN (My University, 2007)
Background The development of multidisciplinary team meetings (MDTMs) for radiology and pathology is a burgeoning area that increasingly impacts on work processes in both of these departments. The aim of this study was to examine work processes and quantify the time demands on radiologists and pathologists associated with MDTM practices at a large teaching hospital. The observations reported in this paper reflect a general trend affecting hospitals and our conclusions will have relevance for others implementing clinical practice guidelines. Methods For one month, all work related to clinical meetings between pathology and radiology with clinical staff was documented and later analysed. Results The number of meetings to which pathology and radiology contribute at a large university teaching hospital, ranges from two to eight per day, excluding grand rounds, and amounts to approximately 50 meetings per month for each department. For one month, over 300 h were spent by pathologists and radiologists on 81 meetings, where almost 1000 patients were discussed. For each meeting hour, there were, on average, 2.4 pathology hours and 2 radiology hours spent in preparation. Two to three meetings per week are conducted over a teleconferencing link. Average meeting time is 1 h. Preparation time per meeting ranges from 0.3 to 6 h for pathology, and 0.5 to 4 for radiology. The review process in preparation for meetings improves internal quality standards. Materials produced externally (for example imaging) can amount to almost 50% of the material to be reviewed on a single patient. The number of meetings per month has increased by 50% over the past two years. Further increase is expected in both the numbers and duration of meetings when scheduling issues are resolved. A changing trend in the management of referred patients with the development of MDTMs and the introduction of teleconferencing was noted. Conclusion Difficulties are being experienced by pathology and radiology departments participating fully in several multidisciplinary teams. Time spent at meetings, and in preparation for MDTMs is significant. Issues of timing and the coordination of materials to be reviewed are sometimes irreconcilable. The exchange of patient materials with outside institutions is a cause for concern when full data are not made available in a timely fashion. The process of preparation for meetings is having a positive influence on quality, but more resources are needed in pathology and radiology to realise the full benefits of multidisciplinary team working.
PUBLISHED
Keywords: workflow